Progression of kidney injury with the combination of vancomycin and piperacillin-tazobactam or cefepime in sepsis-associated acute kidney injury - Whitenack, Kaylee; Behal, Michael L.; Thompson Bastin, Melissa L.; Aycinena, Juan C.; Adams, Paul M.; Flannery, Alexander H. (Frontiers in Nephrology, 2022)
Introduction: The combination of vancomycin/piperacillin-tazobactam is associated with increases in serum creatinine compared to other antibiotic combinations in the treatment of infections for hospitalized patients. However, the available literature is limited to the study of incident acute kidney injury (AKI). The combination has not been evaluated in patients with AKI already present and the degree to which the trajectory of AKI is influenced by this combination is unknown. Methods: This was a single center, retrospective cohort study of adult patients with sepsis and AKI present on admission prescribed a combination of vancomycin with either piperacillin-tazobactam or cefepime within the first 3 days of admission. The primary outcome was maximum serum creatinine observed within days 2-7 of the hospital stay. Subsequent kidney outcomes were evaluated at one week and hospital discharge. Results: Of 480 patients with sepsis and AKI who met inclusion criteria, 288 (60%) received vancomycin/piperacillin-tazobactam, and 192 (40%) received vancomycin/cefepime. Patients were well-matched on clinical factorsat baseline, including severity of illness, stage of AKI, exposure to other nephrotoxins, and durations of antimicrobial therapy. There were no differences in AKI trajectory during over the course of the first week as assessed by maximum serum creatinine (2.1 (1.4-3.5) mg/dl vs. 2.1 (1.4-3.0) mg/dl; p=0.459) and AKI progression (24.0% vs. 23.4%; p=0.895). No differences were observed with other kidney related outcomes, including the need for dialysis (14.6% vs. 13.0%; p=0.628) or major adverse kidney events at hospital discharge (48.3% vs. 47.9%; p=0.941). Conclusions: In patients with sepsis and AKI, the combination of vancomycin/piperacillin-tazobactam compared to vancomycin/cefepime was not associated with higher serum creatinine values or AKI progression in the week following ICU admission.